PENGARUH KECERDASAN EMOSIONAL, MOTIVASI KERJA DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN LABUHANBATU SELATAN - Rafidi M. Noor; Nurliana .; Umar Nafi; Jonny Hutasoit; Juliawan Samsir Rajagukguk (Manajemen dan Bisnis, 2021)
Problem of this study how influence of emotional intellegence on performance. How influence of    job motivation on performance. How influence of  quality work of life on  performance. How influence emotional intellegence,    job motivation and  quality work of life on   performance. The purpose of this study to determine and analyze the effect of  emotional intellegence on   performance. Determine and analyze the effect of   job motivation on   performance. Determine and analyze the effect of  quality work of life on   performance. Determine and analyze the effect of  emotional intellegence,  job motivation and  quality work of life on   performance.  Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate emotional intellegence variable has a positive and significant effect on performance.  job motivation variable has a positive and significant effect on   performance.  quality work of life variable has a positive and significant effect on performance. Emotional intellegence,  job motivation and  quality work of life variable has a positive and significant effect on   performance.